Identification of a Genetically Linked but Functionally Independent Two-Component System Important for Cell Division of the Rice Pathogen Burkholderia glumae - Marunga, Joan; Goo, Eunhye; Kang, Yongsung; Hwang, Ingyu (Frontiers in Microbiology, 2021)
Bacterial two-component regulatory systems control the expression of sets of genes to coordinate physiological functions in response to environmental cues. Here, we report a genetically linked but functionally unpaired two-component system comprising the sensor kinase GluS (BGLU_1G13350) and the response regulator GluR (BGLU_1G13360) is critical for cell division in the rice pathogen Burkholderia glumae BGR1. The gluR null mutant, unlike the gluS mutant, formed filamentous cells in Luria–Bertani medium and was sensitive to exposure to 42C. Expression of genes responsible for cell division and cell-wall (dcw) biosynthesis in the gluR mutant was elevated at transcription levels compared to the wild type. GluR-His bound to the putative promoter regions of ftsA and ftsZ, indicating that repression of genes in the dcw cluster by GluR is critical for cell division in B. glumae. The gluR mutant did not form filamentous cells in M9 minimal medium, whereas exogenous addition of glutamine or glutamate to the medium induced filamentous cell formation. These results indicate that glutamine and glutamate influence GluR-mediated cell division in B. glumae. The fact that GluR controls cell division of B. glumae in a nutrition-dependent manner provides insight into how the recognition of external signals by TCS affects the sophisticated molecular mechanisms involved in controlling bacterial cell division.